Surface site density and utilization of platinum group metal (PGM)-free Fe–NC and FeNi–NC electrocatalysts for the oxygen reduction reaction. Issue 1 (5th November 2020) - Luo, Fang; Wagner, Stephan; Onishi, Ichiro; Selve, Sören; Li, Shuang; Ju, Wen; Wang, Huan; Steinberg, Julian; Thomas, Arne; Kramm, Ulrike I.; Strasser, Peter
Abstract : The gravimetric surface density and ORR catalytic turnover frequency of Fe–NC and Fe/Ni–NC catalysts were investigated. Both catalysts feature chemically identical Fe sites, but the presence of Ni lowered the gravimetric surface density of Fe sites. Abstract : Pyrolyzed iron-based platinum group metal (PGM)-free nitrogen-doped single site carbon catalysts (Fe–NC) are possible alternatives to platinum-based carbon catalysts for the oxygen reduction reaction (ORR). Bimetallic PGM-free M1 M2 –NC catalysts and their active sites, however, have been poorly studied to date. The present study explores the active accessible sites of mono- and bimetallic Fe–NC and FeNi–NC catalysts. Combining CO cryo chemisorption, X-ray absorption and 57 Fe Mössbauer spectroscopy, we evaluate the number and chemical state of metal sites at the surface of the catalysts along with an estimate of their dispersion and utilization. Fe L3, 2 -edge X-ray adsorption spectra, Mössbauer spectra and CO desorption all suggested an essentially identical nature of Fe sites in both monometallic Fe–NC and bimetallic FeNi–NC; however, Ni blocks the formation of active sites during the pyrolysis and thus causes a sharp reduction in the accessible metal site density, while with only a minor direct participation as a catalytic site in the final catalyst. We also use the site density utilization factor, ϕ SDsurface/bulk, as a measure of the metal site dispersion in PGM-free ORR catalysts. ϕ SDsurface/bulk enables a quantitative evaluation and comparison of distinct catalyst synthesis routes in terms of their ratio of accessible metal sites. It gives guidance for further optimization of the accessible site density of M–NC catalysts.